Effectiveness of The Riliv Mindfulness App on Anxiety Among Hypertensive Patients: A Quasi-Experimental Study - Nur Banati Ritriana; Diana Tri Lestari; Sukarmin (Indonesian Journal of Nursing Research (IJNR), 2026)
Hypertension affects both physical and psychological health, including increasing anxiety, which can further worsen patients’ conditions. The Riliv application offers a practical solution for managing anxiety independently and effectively. The purpose of this study was to determine the effect of implementing the Riliv mindfulness application on anxiety levels in hypertensive patients. This study employed a quantitative approach with a pretest–posttest control group design using a quasi-experimental method. The sample was selected through purposive sampling and consisted of 30 respondents, divided into 15 respondents in the intervention group and 15 respondents in the control group. The intervention was conducted over a period of 10 days with 10 sessions using the Riliv mindfulness application. Anxiety levels were measured using the Hamilton Anxiety Rating Scale (HARS) as the primary instrument. Data analysis was performed using paired t-test and independent t-test. The results showed that in the intervention group, the mean anxiety score decreased from 18.27 to 15.73 (p < 0.001). While the control group showed an increase in the mean anxiety score from 18.27 to 18.67 (p = 0.189). The independent t-test results indicated a statistically significant difference in anxiety levels between the intervention group and the control group, with a p-value of 0.005 (p < 0.05). The Riliv mindfulness app significantly reduced anxiety scores in hypertensive patients after 10 days of intervention.